(untitled) (Scientific Researches in Academia, 2024)
The reflective practice recalls our past experiences, reveals reality, and realizes the strengths and weaknesses of the practitioner while changing its abstract idea into practical action. In a similar line, this paper explored the concept of reflective practices and its implications in the classroom. The main purpose of this study was to investigate ways of reflective practices applied by language teachers in their profession reviewing various perspectives on its practices. The information of this study was generated through secondary sources and interviews of research participants; three English teachers of public schools from different parts of Nepal. The result of this study indicated that practice enables teachers to make more informed decisions about their teaching and, as a result, their reflective students receive the best possible opportunities for their learning. Hence, the study’s findings will guide pre-service and in-service English language teachers to grow their careers, especially in the teaching field.